Protection of Commercial Cargo Ships in the Exercise of the Right of Passage Through International Straits - Satriya Nugraha; Rengga Kusuma Putra; Dewa Gede Sudika Mangku; Aziz Widhi Nugroho; Rianmahardhika Sahid Budiharseno (Jurnal Ilmiah Dunia Hukum, 2026)
As time goes by and the development of the ship industry, international straits also play an important role as vital routes for the movement of ships. UNCLOS 1982 regulates the use of international straits as international navigation routes, affirming the importance of the Strait in global trade. The Strait is a transportation route and a source of significant economic potential, supporting growth and investment in the surrounding area. However, there are often dynamics and conflicts with countries on the edge of the Strait, one of which is the case of the Yemeni militant Hothi, who attacked merchant ships heading to the Americas and Europe or vice versa. Therefore, it is important to know about the rights and obligations of strait states in the context of maritime law and maritime law. This study will examine the regulation of the protection of commercial cargo ships in the peaceful passage of international straits and the protection of commercial cargo ships that have been attacked by a country's military group in international waters, with a legal research method that will analyze and provide a prescriptive view. UNCLOS 1982 regulates the peaceful passage of commercial cargo ships in the international Strait with the principle of freedom of navigation. It guarantees the safety of navigation, but there are restrictions to maintain the peace of coastal states that must still be observed. Ship protection involves the responsibility of coastal states, which must ensure unimpeded peaceful passage and provide hazard notices. Additional regulations such as SOLAS 1974 set minimum safety standards. Military attacks on commercial cargo ships could cause diplomatic tensions and economic losses. International cooperation, strict law enforcement, and mutual security measures are needed to enhance protection. This joint effort, involving coastal states and international cooperation, is expected to create a safe and stable maritime environment.